Some Aspects Of The Biology Of Lernaea Gonionoti Sp.Nov (Crustacea: Copepoda) And L. Cyprinacea Linnaeus In Puntius Gonionotus (Bleeker). - Kularatne, M. (1993)
Lernaea is among the most important crustacean parasites of freshwater fish which poses a serious threat to Malaysian aquaculture . An outbreak of lernaeosis occurred in a manmade lake in the Shah Alam recreational park in Selangor Darul Ehsan , West Malaysia during early 1991 and caused severe mortalities of Javanese carp ( Puntius gonionotus ) , locally known as Lampam Jawa . The parasite involved was identified as a new lernaeid species specific to P.gonionotus and named as Lernaea gonionoti sp. nov . It was found that L. gonionoti sp . nov . can be differentiated from other known Malaysian lernaeid parasites during their early life , using certain larval morphometrics , especially the body length . However , on P.gonionotus , L . cyprinacea and L . gonionoti sp . nov . have a similar duration for their early life stages.